2006
DOI: 10.1016/j.jeconom.2005.01.016
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of the usefulness of ARFIMA models for predicting macroeconomic and financial time series

Abstract: This paper addresses the notion that many fractional I(d) processes may fall into the "empty box" category, as discussed in Granger (1999). We begin by showing that so-called spurious long memory may arise not only in the presence of (stochastic) structural breaks and regime switches, but also when the true data generating processes (DGPs) are linear with no structural breaks, and/or regime switching properties. However, we also present ex ante forecasting evidence based on an updated version of the absolute r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 66 publications
4
61
1
Order By: Relevance
“…LOP weights in Figure 5 show that there is some uncertainty at the beginning of the sample, but after September 2007 Abbassi and Linzert (2011), where the mean of the series shifts upward and volatility is high but less than for the previous period. We find as in Bhardwaj and Swanson (2006) that ARFIMA models produce accurate forecasts when there are several stochastic and unknown structural breaks. Which ARFIMA model to use is however unclear ex-ante; LOP can cope with such uncertainty and mixing predictive density can also approximate different regimes over time caused by different types of shocks.…”
Section: Forecast Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…LOP weights in Figure 5 show that there is some uncertainty at the beginning of the sample, but after September 2007 Abbassi and Linzert (2011), where the mean of the series shifts upward and volatility is high but less than for the previous period. We find as in Bhardwaj and Swanson (2006) that ARFIMA models produce accurate forecasts when there are several stochastic and unknown structural breaks. Which ARFIMA model to use is however unclear ex-ante; LOP can cope with such uncertainty and mixing predictive density can also approximate different regimes over time caused by different types of shocks.…”
Section: Forecast Resultsmentioning
confidence: 55%
“…We require 0 < d < 1, forecasting exercises when the data sample is small. Moreover, spurious long memory behaviors arise in many contexts, such as when there are (stochastic) structural breaks in linear and nonlinear models, regime switching models, and when forming models using variables that are nonlinear transformations of underlying "short memory" variables, see for example Byers et al (1997), Diebold and Inoue (2001), Engle and Smith (1999) and Bhardwaj and Swanson (2006).…”
Section: Individual Modelsmentioning
confidence: 99%
“…These data were used by Bhardwaj and Swanson (2005), who applied ARFIMA models to the series and found that the latter frequently outperform linear models in terms of prediction. In their paper, the authors suggested, as an interesting extension to their work, to see whether nonlinear models with regime-switching or thresholds would perform better than the ARFIMA models.…”
Section: Application To Absolute and Squared Returnsmentioning
confidence: 99%
“…3 Bhardwaj and Swanson (2006) challenged this evidence by showing that ARFIMA models estimated using a variety of standard estimation procedures yield ''approximations'' to the true unknown underlying DGP. These in turn can sometimes provide significantly better out-of-sample predictions than simple linear non-ARFIMA models such MA, ARMA GARCH among others, when evaluated on the basis of point MSFE's as well as on the predictive accuracy tests and t-tests.…”
mentioning
confidence: 99%
“…Understanding of the dynamic behavior of stock returns in these markets is crucial for portfolio managers, policy makers, and researchers. Therefore, the current paper attempts to add to the limited volume of literature on the usefulness of long-memory models in predicting stock 3 By "empty box", Granger means ARFIMA models have stochastic properties that essentially do not mimic the properties of the data (Bhardwaj and Swanson, 2006). …”
mentioning
confidence: 99%